Resumption and progression of meiosis and circulating levels of steroids and prostaglandin F2α of Piaractus mesopotamicus induced by hypophysation with prostaglandin F2α - Sato, Rafael Tomoda [UNESP]; Kuradomi, Rafael Yutaka; Calil, Marina Cabral [UNESP]; de Jesus Silva, Laiza Maria [UNESP]; de Abreu, Mariana Roza [UNESP]; Figueiredo-Ariki, Daniel Guimarães [UNESP]; de Freitas, Guilherme Antônio [UNESP]; Batlouni, Sergio Ricardo [UNESP] (Hindawi, 2021)
We have previously shown an increase on the ovulation rate of pacu, Piaractus mesopotamicus, using hypophysation with prostaglandin F2α (PGF2α) (HPG protocol) rather than hypophysation (H); only, however, a persistent lack of ovulation in some females could not be further explained by PGF2α and steroid plasma levels at time of ovulation. Considering this, here we compared the meiotic process and steroids and PGF2α levels during spawning induction using both protocols. To that, H and HPG were treated with conventional hypophysation (0.6 mg/kg priming and 5.4 mg/kg resolving dose), and the latter received synthetic PGF2α (2 mL/fish) at resolving dose. A negative control (saline solution), a SPG group (receiving only PGF2α) and a PPG group (receiving priming and PGF2α) were included. An initial PGF2α peak between one to four hours post-resolving dose (1-4 hr) occurred in groups receiving PGF2α (HPG, SPG and PPG). Only H and HPG showed a 17α-20β-dihydroxy-4-pregnen-3-one (DHP) peak 4 hr, concomitant with meiosis resumption, and a final PGF2α peak 12 hours. The HPG protocol resulted in higher PGF2α plasma levels for longer periods (1-4 and 12 hr) than H (single peak 12 hr), occasioning in the former higher and concomitant levels of both PGF2α and DHP at 4 h. Considering that DHP is known to induce expression of prostaglandin receptors in fish, the concomitant plasma peaks of DHP and PGF2α may also explain the ovulation rate gain previously published, using HPG protocol, which can be further improved adjusting the priming dose and defining the exact interval of PGF2α ovulatory action in this species.
Keywords: DHP; hormonal induction; plasma profile; priming dose; prostaglandin